A proposed library media center for the University of the Philippines Integrated School - Santos, Teresita D.; Buenrostro, Juan Jr. C.; Castillo, Jovito B. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1993)
This study proposes the organization of a media center in the UPIS. The initial task was to determine the current status of audiovisual resources at the UP Integrated School and their utilization by the faculty. It proceed to : a) establish the objectives and functions of a media center in the UPIS Library in relation to the mission objectives of the school; b) identify the needs to establish a media center for the faculty and students; c) determine the needed improvement in physical facilities and resources, and d) formulate policies and procedures that govern the administration of the center.
The descriptive method was used in this study. Two sets of questionnaire were used: one for the 15 heads/administrators and another for the 90 faculty members of the UPIS. These questionnaires were the primary tools used for data gathering supplemented by interviews and actual observations. Secondary sources were consulted such as the records of the Human Resource Development Office particularly in hiring media personnel.
The survey findings indicated that: 1) there is a need to establish a media center within the UPIS. The audiovisuals, facilities and systems of services in the UPIS are evidently not enough to meet the teaching needs of the school; 2) utilization of newer media resources is not maximized due to the lack of awareness by the faculty of their existence. Lack of newer media resources and equipment to service them also explain this low utilization; 3) there is a need to organize the audiovisuals in the school for more effective and efficient use. A union list of audiovisual resources are urgently needed; 4) the faculty members lack courses in audiovisual education as well as training in relation to media utilization; 5) there is no budget specifically appropriated for media services in the school.
It is evident from the results of the study that the UPIS should establish a media center responsible for the organization and management of audiovisual resources in order to fulfill its vital role as a partner of the university's instructional program.
Typescript
Vita.
Special Problem (Master of Library Science)
Keywords: Audiovisual materials -- Philippines -- Quezon City; Instructional materials centers; Media centers See Instructional materials centers; University of the Philippines Integrated School